An analysis of gender difference on students’ misconceptions in learning the material classification and its changes - Muhammad Agung Safari Cahyanto; Ashadi Ashadi; Sulistyo Saputro (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2019)
Every teacher has experiences to identify and find out students who have misconceptions in their classrooms. Misconceptions that occur can differ between male and female students. The purpose of this study was to analyze the effect of gender on misconceptions in the lesson of the material classification and its changes. The survey-aiming method was used in this study. A total of 62 students from one of the state junior high schools in the city of Surakarta consisting of 34 male students and 28 female students were involved as the subjects in this study. Identification of misconceptions was conducted using the Two-tier multiple-choice diagnostic instrument that was equipped with the Certainty of Response Index method. The formulation of this study problem was: “How are the differences of misconceptions between male and female students in learning the material classification and its changes?” This study showed that female students tended to have misconceptions on the competency achievement indicator vis-a-vis explaining the understanding of elements, compounds and mixtures, while male students tended to have misconceptions on the competency achievement indicator pertinent to distinguishing elements, compounds, and mixtures. In general, female students had better conceptual knowledge than male students. The two-tier multiple-choice instrument could be used as an alternative instrument to identify misconceptions among students. The results of this study are expected to be a reference for educators to identify and resolve students’ misconceptions.